Angiography of renal artery with special reference to the blood supply of the kidney in camel - ANURADHA, ANURADHA; JAIN, R K; GUPTA, A N (The Indian Journal of Animal Sciences, 2014)
The vascular system of kidney of the camel is strikingly different from that of other domestic animals. The right and left renal arteries cmanated independently from the ventrolateral aspect of abdominal aorta behind cranial mesenteric artery at the level of cranial border of third and fourth lumbar vertebra respectively. The renal artery after short lateral course divided mto medial and lateral lobar arteries before reaching the hilus. The lobar artery after entering into the hilus gave 9-11 interlobar arteries. These interlobar arteries at the eorticomedullary junction formed 2 - 7 arcuate arteries. The arcuate arteries detached numerous straight branches from their convex surfaces and then ended by dividing into 2 - 4 terminal branches. The straight branches and the terminal branches were present in a radiating manner as interlobular arteries.